Breeding value of leafy and root turnip samples from the VIR collection - D. L. Kornyukhin; A. M. Artemyeva (Овощи России, 2022)
Turnip, Brassica rapa L. subsp. rapa is the oldest vegetable crop in Russia. Turnip varieties are fastgrowing, productive, have valuable biochemical properties, cold-resistant, relatively easy to grow. To expand the vegetable assortment, new varieties and hybrids should be created, first of all, the types of varieties that are not in the State Register of Russia. The purpose of the work: using the data of a long-term study of the VIR collection to identify valuable material for breeding.Methods. Field study of 170 samples of the VIR collection was carried out in the NPB "Pushkin and Pavlovsk laboratories of VIR" (Leningrad region) in 2001-2020. Sowing was carried out on June 26- 28. Each sample was sown on a single-row plot 2 m long in three repetitions. As a control, turnip varieties included in the State Register were used – the variety of leaf turnip Sapphire, the table turnip variety Petrovskaya-1 and the fodder turnip variety Osterzundomsky. The description was carried out according to the Methodological Guidelines for the study and maintenance of the VIR world collection, with author's additions.Results. The best leaf turnip samples, found during the study has a large plant mass (up to 1.42±0.32 kg in the Early top F1 sample (k-366, Japan), many samples exceeded the Sapphire standard for this trait. Some of the samples of table turnips also exceed the Petrovskaya-1 standard by weight of the root (Purple top (k-1345, Nepal), Pekki (vr.2176, Finland)). Samples Solovetskaya (k-803, Russia, Murmansk region), Gul Findlandsk (vr.2175, Norway) have a bright yellow flash of the root, are easy to store and resistant to damage by cabbage flies. Among the turnip samples distinguished by yield (Table 5), the most interesting are the turnips Ova Dæhnfeldt (vr.2183, Denmark) and Korova (vr.2187, Sweden), which have yellow flesh and an increased content of β-carotene in roots.Conclusion. It was possible to identify new samples belonging to groups of leaf and root turnips, that are not represented on the seed and food market of Russia. Such samples belong to morphologically different forms, are productive, carry a complex of valuable economic and biochemical characteristics and are perspective material for inclusion in programs for the selection of leaf and root crops.